Up2B2: Playing English grammar games at the B2 level - lvalue lvalue (Universitat Jaume I. Department of English Studies, 2018)
Author/s Irina Argüelles Álvarez Margarita Martínez Núñez Ana Belén García Hernando Antonio da Silva Fariña Universidad Politécnica de Madrid, Spain   ABSTRACT The study presented herein is framed within the Mobile Assisted Language Learning (MALL) approach and presents the results from the use of an original mobile app, developed by the research team, on the part of 73 students. The app prototype consists of multiple choice questions and answers that assess varied aspects of the grammar, vocabulary and use of English at level B2 according to the Common European Framework of Reference for Languages (CEFRL). The application presents motivating gamification components that aim at enhancing students' participation and regular use of the game. Some of these gamification features are response time, use of competition and training tests, and a score ranking based on nicknames. The study uses different indexes in order to describe the use of the platform and qualitative and quantitative indicators to reach positive conclusions related to students' increased motivation and improvement in their grammar and vocabulary competence levels.